Psychological Correlates of Achievement Motivation on the Personal-meaning Level - Berdnikova, D (KnE Life Sciences, 2018)
This article is devoted to the study of psychological correlates of the achievement motivation on the personal-meaning level of the first-year psychology students. The author revealed a wide range of psychological correlates of achievement motivation: value orientations (universal values, power, self-development, etc.), the parameters of existential fulfillment (self-transcendence, freedom, etc.) and the general level of life meaningfulness, self-actualization parameters (creativity, self-acceptance, spontaneity, etc.). Based on the conducted correlation research, the author developed a training program aimed at actualization and growth in the motivation of the firstyear psychology students. The study involved experimental and control groups. In the course of the study, when comparing the data of preliminary and final testing, the dynamics of achievement motivation indicators in the experimental group was revealed in the direction of increasing the achievement motivation, while in the control group there were no significant differences in the level of achievement motivation, which indicates the effectiveness of the training developed by author. At the same time, it is shown that the growth of the achievement motivation occurred due to the growth of its transcendent component, which is a good indicator, since psychology students with high motivation of transcendence are predominantly oriented toward acquiring knowledge and mastering the profession. The data obtained in the study enriches author’s understanding of the psychological phenomenon, such as achievement motivation, and have applied significance: the training program developed by the author can be used to increase the achievement motivation of students and can also be tested on another contingent. Keywords: achievement motivation, value orientations, existential fulfillment, self-actualization, psychology students